KINSHIP TERMS USED BY STRANGERS TOWARDS TWO OFFSPRINGS OF INTER-ETHNIC MARRIED COUPLES IN SURABAYA - Dinda Mutiara; Esther H Kuntjara (Kata Kita: Journal of Language, Literature, and Teaching, 2014)
This research investigates the kinship terms produced by strangers towards two young offsprings of inter-ethnic married couples who were used as enticements to generate the production along with the social factors. The data taken from both natural conversations and informal conversational interviews were analyzed using the theories of address Indonesian in Indonesian (John & Stokes, 1977), Javanese (Kuntjara, 2001), Dutch (Matres & Sekel, 2007), and those produced by Chinese-Indonesian (Kuntjara, 2009) and social factors proposed by Holmes (1992) and Wardhaugh (2006). The findings resulted in the mixture of kinship terms from Indonesian, Javanese, Chinese, Dutch, and zero address term which were addressed by strangers to M and F. In addition, addressors mostly considered their own aspects, ethnicity, setting, transactional status and function, and prior knowledge and personal preference as the decisive factors when choosing kinship terms. While the addressee’s aspects, physical features and visible appearance, were the minor factors they took into account.